Pharmacokinetics and brain uptake in the rhesus monkey of a fusion protein of arylsulfatase a and a monoclonal antibody against the human insulin receptor. Issue 5 (25th December 2012) - Boado, Ruben J.; Lu, Jeff Zhiqiang; Hui, Eric K.‐W.; Sumbria, Rachita K.; Pardridge, William M.
Abstract Metachromatic leukodystrophy (MLD) is a lysosomal storage disorder of the brain caused by mutations in the gene encoding the lysosomal sulfatase, arylsulfatase A (ASA). It is not possible to treat the brain in MLD with recombinant ASA, because the enzyme does not cross the blood‐brain barrier (BBB). In the present investigation, a BBB‐penetrating IgG‐ASA fusion protein is engineered and expressed, where the ASA monomer is fused to the carboxyl terminus of each heavy chain of an engineered monoclonal antibody (MAb) against the human insulin receptor (HIR). The HIRMAb crosses the BBB via receptor‐mediated transport on the endogenous BBB insulin receptor, and acts as a molecular Trojan horse to ferry the ASA into brain from blood. The HIRMAb‐ASA is expressed in stably transfected Chinese hamster ovary cells grown in serum free medium, and purified by protein A affinity chromatography. The fusion protein retains high affinity binding to the HIR, EC50 = 0.34 ± 0.11 nM, and retains high ASA enzyme activity, 20 ± 1 units/mg. The HIRMAb‐ASA fusion protein is endocytosed and triaged to the lysosomal compartment in MLD fibroblasts. The fusion protein was radio‐labeled with the Bolton–Hunter reagent, and the [125I]‐HIRMAb‐ASA rapidly penetrates the brain in the Rhesus monkey following intravenous administration. Film and emulsion autoradiography of primate brain shows global distribution of the fusion protein throughout the monkey brain. These studies describe a new biological entity that is designed to treat the brain of humans with MLD following non‐invasive, intravenous infusion of an IgG‐ASA fusion protein. Biotechnol. Bioeng. 2013; 110: 1456–1465. © 2012 Wiley Periodicals, Inc.